Cuantificación de glucosa producida en el hidrolizado enzimático de la biomasa lignocelulósica (cáscara de arroz) - Rogel Alban, Karen Andrea (2017)
The objective of the present investigation was to quantify the glucose level produced in the enzymatic hydrolysis of the lignocellulosic biomass from one of the most important agroindustrial residues that Ecuador has, which is the rice husk, which is a plant tissue composed of Lignin, cellulose and hemicellulose, so it is considered an adequate substrate for sugar production given its availability and relative low cost. For its transformation into reducing sugars, the fungus Trichoderma reesei was used, that produces enzymes called cellulases that hydrolyze the celluloses. Some of the most important cellulolytic enzymes are: endoglucanase (hydrolyze β- (1-4) bonds randomly through cellulose microfibers), exoglucanases (remove cellulose monomers one at a time at the end of the polymer) and β-glucosidases (Break the β- (1-4) bonds between the cellulose monomers but generate a disaccharide called cellobiose), finding that the optimum temperature of growth of said fungus is around 22 to 30 °C, because they are aerobic require Of an oxygen source and tolerate a wide pH range (2 - 8.5), to activate Trichoderma reesei, 2 % of fungus was added in a 4 % (w/v) culture medium (Carboxymethylcellulose - deionized water) by incubating For 5 hours at 35 ° C. In order to determine the potential utilization of the rice husk as a growth medium for the growth of the fungus for the enzymatic hydrolysis of cellulose glucose, 4 culture media (ground rice husk and deionized water) were prepared in biorreactors Of capacity of 2000 ml; with concentrations of 21 % (w/v) and 100 ml of the CMC activated inoculum, using substrates of two different particle sizes (425 and 850 μm), which were inoculated with conidia of the fungus Trichoderma reesei in two concentrations (1, 5 g/l and 2 g/l), resulting in a 2 x 2 factorial design, where it hydrolysed for 240 hours at room temperature and pH 6.5-7. However, for an adequate sugar production process, Necessary the application of pre-treatments that modify the complex structure of this material. The pretreatment used was the grinding of the lignocellulosic materials by a combination of chipping and milling, reducing the crystallinity of the cellulose, increasing the specific surface area and bulk density, facilitating the enzymatic hydrolysis. The present experiment was carried out in the Electrochemical laboratory of the Universidad Técnica de Machala where the reducing sugars were measured using the DNS method (di-nitrosalisylic acid) in a visible UV spectrophotometer. Based on the results obtained, it was concluded that the treatment with the highest percentage of bioconversion was the one that had a particle size of 425 μm and a concentration of 2 g/l of inoculum, corresponding to treatment C, in which a Glucose level of 458 mg/l, with a pH of 5.2 and 0.5 dissolved oxygen as the fungus is an aerobic microorganism begins to consume oxygen from the moment it is inoculated to the culture medium.